PENGARUH KUALITAS SUMBER DAYA MANUSIA, PROFESIONALISME KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN CABANG MEDAN DENAI - Novita Sari Hasibuan; Yayuk Yuliana (Jurnal Inovasi Penelitian, 2023)
This study aims to determine the effect of the quality of human resources, work professionalism and commitment to employee performance at PT. PLN (Persero) Medan Branch Customer Service Unit. This research is a quantitative research. Respondents who became the sample in this study amounted to 60 respondents. The data used in this study are primary data obtained through questionnaires, interviews, field observations and documentation. Data processing and statistical analysis used the SPSS and Microsoft Excel programs with a significance level of 0.05. The results of the validity and reliability tests, all research instruments are valid, valid and reliable. The data analysis technique used is the coefficient of determination test (R2) through multiple linear regression tests. The statistical test results in this study stated that the variables of human resource quality (X1), work professionalism (X2), commitment (X3) were able to explain employee performance (Y) by 51.6% while the remaining 48.4% were influenced or explained by variables which were not included in this research model. From the Coefficientsa table, the multiple linear regression equation Y = 8.698 + 0.928 + 0.600 + 0.857 is obtained. Partially the quality of human resources (X1) has a significant effect on employee performance (Y), work professionalism (X2) has a significant effect on employee performance (Y), commitment (X3) has a significant effect on employee performance (Y). Simultaneously the quality of human resources (X1), work professionalism (X2), commitment (X3) together have a significant influence on employee performance (Y).